Analisa Performance Instalasi Radiologi Dalam Upaya Pemenuhan Standar Pelayanan Minimal (Spm) Di Rumah Sakit Condong Catur Yogyakarta - Dewi Ariyani Wulandari; Tedy Candra Lesmana (Jurnal Manajemen Kesehatan Indonesia, 2021)
Radiology services are an integrated part of overall health services. Radiology is a supporting examination to establish disease diagnosis and provide prompt and appropriate therapy for patients. Analysis of the results of radiology at the Condong Catur Hospital found that an average of 74 (86.80%) files from patients were in accordance with the standards and 12 files from patients (13.20%) were not in accordance with predetermined standards. These problems will interfere with the service quality and performance of the hospital. The purpose of this study was to evaluate the implementation of the Minimum Service Standards or Standar Pelayanan Minimal (SPM) Policy of the radiology unit at the Condong Catur Hospital Yogyakarta. This type of research is qualitative with a case study design. The key informants were radiographers, medical doctor of radiology specialists, and chief medical officer. Data collection methods consisted of observation methods, in-depth interviews and documentaries. This research shows that the policies and commitments have been formed, but the resources are only sufficient for the minimum requirement. The application has referred to the radiology service policy, bureaucratic structure, compliance with clinical practice guidelines and standard operating procedures. Process components that support the success of radiology services are the disposition (attitude) and communication patterns between top management and staff in implementing SPM for radiology services that have been running quite well, but some have not reached the target. The suggestion of this research is that the management always socializes minimum service standards policy and standard operating procedures radiology to improve radiology services.